Characterization of Two ENU-Induced Mutations Affecting Mouse Skeletal Morphology - Dauphinee, Shauna M. (Genetics Society of America, 2013)
Using the N-ethyl-N-nitrosourea (ENU) mutagenesis screen, we have identified two skeletal morphology mutants, Skm1 and Skm2. Positional cloning and candidate gene sequencing localized the causative point mutations within the genes coding for natriuretic peptide receptor C (NPR-C) and filamin b (FLNB), respectively. Mice that carry a mutation in Npr3 exhibit a skeletal overgrowth phenotype, resulting in an elongated body and kyphosis. Skm2 mice, carrying a mutation in Flnb, present with scoliosis and lordosis. These mutant mice will serve as useful models for the study of vertebral malformations.